Effects of zinc application on cadmium (Cd) accumulation and plant growth through modulation of the antioxidant system and translocation of Cd in low- and high-Cd wheat cultivars. (October 2020) - Zhou, Jun; Zhang, Chen; Du, Buyun; Cui, Hongbiao; Fan, Xingjun; Zhou, Dongmei; Zhou, Jing
Abstract: Cadmium (Cd) contamination is a big challenge for managing food supply and safety around the world. Reduction of the bioaccumulation of cadmium (Cd) in wheat is an important way to minimize Cd hazards to human health. This study compared and highlighted the effects of soil and foliar applications of Zn on Cd accumulation and toxicity in cultivars with high Cd accumulation (high-Cd wheat) and low Cd accumulation (low-Cd wheat). Both foliar and soil Zn applications provided effective strategies for reducing wheat grain Cd concentrations in the high-Cd wheat by 26–49% and 25–52%, respectively, and these also significantly reduced the concentrations in wheat stems and leaves. Foliar and soil Zn applications significantly reduced Cd in leaves and stems of the low-Cd wheat but had no effects on grain Cd. Both soil and foliar Zn applications significantly alleviated Cd toxicity by regulation of Cd transport genes, as reflected by the increased grain yield and antioxidant enzyme activity in the wheat tissues. Gene expression in response to zinc application differed in the two wheat cultivars. Down-regulation of the influx transporter ( TaNramp5 ) and upregulation of the efflux transporters ( TaTM20 and TaHMA3 ) in the high-Cd wheat may have contributed to the Zn-dependent Cd alleviation and enhanced its tolerance to Cd toxicity. Additionally, foliar Zn applications down-regulated the leaf TaHMA2 expression that reduced root Cd translocation to shoots, while soil Zn applications down-regulated the root TaLCT1 expression, which contributed to the reduction of root Cd concentrations. Soil (99 kg ZnSO4 ·7H2 O ha −1 ) and foliar (0.36 kg ZnSO4 ·7H2 O ha −1 ) Zn applications can effectively decrease the Cd in grains and guarantee food safety and yield, simultaneously. The presented results provide a new insight into the mechanisms of, and strategies for, using Zn for the Cd reduction in wheat. Graphical abstract: Image 1 Highlights: Foliar and soil Zn application effectively increased the yield of the soft wheat variety. Foliar Zn application reduced grain Cd concentrations in wheat of high-Cd accumulation but not durum wheat. Zinc application alleviated Cd-induced oxidative stress by improving antioxidative systems for both wheat. Zinc application downregulated the expression of influx transporter and upregulated efflux transporter in wheat of high-Cd accumulation. Abstract : Zinc application reduced the Cd accumulation in high-Cd wheat grains, but not in low-Cd wheat, due to different patterns of gene expression.